If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 56 = 0 Reorder the terms: 56 + 8x = 0 Solving 56 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 8x = 0 + -56 Combine like terms: 56 + -56 = 0 0 + 8x = 0 + -56 8x = 0 + -56 Combine like terms: 0 + -56 = -56 8x = -56 Divide each side by '8'. x = -7 Simplifying x = -7
| 7-2a=-28+8a | | 10-2(2.5-13.5x)-6x=140-(11x+7) | | 7a+4=28-a | | 5464=656*296 | | -5a-7=28 | | 11-5y=2+y | | 7-a=-28+3a | | -3+2y=3-y | | 5a-7=-28 | | 6-2y=4-3y | | 7-a=28 | | 2(3+2x)=2 | | (1+y)dx=(1-x)dy | | 16(x+3)=142-(4x-11)*6 | | 16(x+2)=142-(4x-11)*6 | | 16x(x+3)=142-(4x-11)*6 | | 16x(x+2)=142-(4x-11)*6 | | z^4-4iz^2-1+4i=0 | | (3x-2y+1)dx+(6x-4y+1)dy=0 | | 72-6x+2y=0 | | 72+6x+2x=0 | | 20-8y=5-3y | | (x+2y+8)dx-(3x-6y+18)dy=0 | | 3(2x-5)(2x+4)= | | 2-3(x-1)=29 | | 8y+26=42 | | 11x=3.1416 | | P=25+3Qs | | 5x+3y=.6 | | log(x+2)-log(x)=12 | | 5x+20=4x-20 | | ((x+2)*(x+2)*(x+2))-(x*x*x)=152 |